A lithium ion battery and an electric device

CN123018072APending Publication Date: 2026-10-30JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611100530.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0002]传统NCM811体系的电池在满电(100% SOC)针刺测试中,通常难以满足不起火、不爆炸、不冒烟的安全要求,成为制约其大规模应用的核心技术瓶颈

Benefits of technology

本发明针对上述技术痛点,提出一种多维协同安全设计策略,核心创新点如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of lithium ion batteries, and more particularly to a lithium ion battery and an electric device. The lithium ion battery comprises a shell, an electrode assembly and an electrolyte accommodated in the shell; the electrode assembly comprises a positive electrode sheet, a negative electrode sheet, a separator and a tab; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode current collector in the thickness direction; the positive electrode active material layer comprises LiNi 0.8 Co 0.1 Mn 0.1 O2、LiMn 0.6 Fe 0.4 PO4、a conductive agent and a binder. By filling the gap between NCM811 particles with LMFP, optimizing the spatial distribution of the PVDF binder, constructing a continuous three-dimensional network structure, the mechanical strength of the positive electrode sheet is significantly improved, and the needle-punching internal short circuit mode is actively controlled from the high-risk current collector-negative electrode active material layer to the safe positive electrode active material layer-negative electrode active material layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a lithium-ion battery and an electrical device. Background Technology

[0002] Traditional NCM811 system batteries typically fail to meet the safety requirements of not catching fire, not exploding, and not emitting smoke in a full-charge (100% SOC) nail penetration test, becoming a core technical bottleneck restricting their large-scale application.

[0003] Currently, existing technologies for improving the needle penetration safety of cylindrical batteries mainly include coating the surface of NCM811 particles with inert oxides such as Al2O3 and ZrO2, coating the surface of PE separators with alumina ceramic layers, adding flame retardant additives to the electrolyte, and modifying the current collector. However, these methods are relatively simple and cannot systematically solve the needle penetration safety problem of cylindrical batteries. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the aforementioned related technologies. Therefore, the present invention provides a lithium-ion battery; wherein the positive electrode active material layer comprises a high-nickel ternary material and LiMn... 0.6 Fe 0.4 PO4 (LMFP); by filling the gaps between high-nickel ternary material particles with LMFP, the spatial distribution of PVDF binder is optimized, a continuous three-dimensional network structure is constructed, the mechanical strength of the positive electrode sheet is significantly improved, and the needle-puncture internal short-circuit mode is actively regulated from the high-risk current collector-negative active material layer to the safe positive active material layer-negative active material layer.

[0005] To address the aforementioned technical problems, in a first aspect, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a housing and an electrode assembly and an electrolyte disposed within the housing; The electrode assembly includes a positive electrode plate, a negative electrode plate, a diaphragm, and tabs; The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector along its thickness direction; the positive active material layer includes a high-nickel ternary material, lithium manganese iron phosphate material, a conductive agent, and a binder; the high-nickel ternary material has the chemical formula LiNi. x Co y Mn z O2, 0.7≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, and x+y+z=1; the chemical formula of the lithium manganese iron phosphate material is LiMn a Fe b PO4, 0.5≤a≤0.7, 0.3≤b≤0.5, and a+b=1.

[0006] In a preferred embodiment, the high-nickel ternary material has the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, the chemical formula of the lithium manganese iron phosphate material is LiMn 0.6 Fe 0.4 PO4.

[0007] In a preferred embodiment, the porosity of the positive electrode current collector is 15% to 25%.

[0008] In a preferred embodiment, the peel strength between the positive electrode active material layer and the positive electrode current collector is ≥28 N / m.

[0009] In a preferred embodiment, the compaction density of the positive electrode active material layer is 3.3 g / cm³. 3 ~3.6g / cm 3 The porosity is 25%~35%.

[0010] In a preferred embodiment, the LiMn 0.6 Fe 0.4 The D50 of PO4 is 200nm~350nm.

[0011] In a preferred embodiment, the LiNi 0.8 Co 0.1 Mn 0.1 The D50 of O2 is 8µm~12µm.

[0012] In a preferred embodiment, the positive electrode active material layer comprises, by mass percentage, 82%-88% high-nickel ternary material, 9%-18% lithium manganese iron phosphate material, 1.2%-1.8% conductive agent, and 1.2%-1.8% binder.

[0013] In a preferred embodiment, the lithium-ion battery is a full-tab lithium-ion battery.

[0014] In a preferred embodiment, the tab has a width coverage of ≥95%, a rated capacity of 5.0Ah~6.0Ah, a charging cut-off voltage of 4.25V, a discharging cut-off voltage of 2.5V, and an ACR internal resistance of ≤5mΩ.

[0015] It should be understood that the lithium-ion battery in this invention adopts a full-tab winding structure; the tabs here include positive tabs and negative tabs, the positive tab is a metal conductive lead-out terminal extended and cut from the positive current collector; the negative tab is a metal conductive lead-out terminal extended and cut from the negative current collector; the tab width coverage of the positive tab and the negative tab is ≥95% respectively.

[0016] In a preferred embodiment, the thickness of the diaphragm is 6µm to 14µm, specifically referring to the total thickness of the diaphragm substrate and coating being 6µm to 14µm.

[0017] In a preferred embodiment, the diaphragm is made of polyethylene.

[0018] In a preferred embodiment, the diaphragm is coated with an alumina-polyimide composite ceramic coating on at least one side along the thickness direction; the thickness of the alumina-polyimide composite ceramic coating is 2µm to 4µm, and the puncture strength is ≥500gf.

[0019] In a preferred embodiment, the diaphragm is coated with a ceramic coating on both sides along its thickness direction.

[0020] In a preferred embodiment, the diaphragm is coated with an alumina-polyimide composite ceramic coating on both sides along the thickness direction.

[0021] In a preferred embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector along its thickness direction; the compaction density of the negative electrode active material layer is 1.5 g / cm³. 3 ~1.7g / cm 3 .

[0022] In a preferred embodiment, the negative electrode active material layer comprises silicon carbon material and graphite; the silicon carbon material accounts for 5%-25% of the mass of the negative electrode active material layer.

[0023] In a preferred embodiment, the electrolyte comprises an electrolyte salt and / or a solvent and / or a film-forming additive; the electrolyte salt comprises lithium hexafluorophosphate; the solvent comprises ethylene carbonate (EC) and / or ethyl methyl carbonate (EMC) and / or dimethyl carbonate (DMC); and the film-forming additive comprises vinylene carbonate (VC) and lithium difluorophosphate (LiPO2F2).

[0024] In a preferred embodiment, the lithium-ion battery, at 100% SOC, undergoes a φ5mm steel needle penetration test at a rate of 5±1mm / s, and does not catch fire, explode, or emit smoke; the maximum surface temperature of the battery is ≤130℃. In a preferred embodiment, the lithium-ion battery has a 1C / 600-cycle capacity retention rate of ≥85.0% and an electrode expansion rate of ≤16% after 600 cycles.

[0025] In a second aspect, the present invention provides an electrical device comprising the lithium-ion battery described in any of the preceding claims.

[0026] Compared with the prior art, the present invention achieves at least the following technical effects: To address the aforementioned technical pain points, this invention proposes a multi-dimensional collaborative security design strategy, with the following core innovations: 1. This invention utilizes nanoscale LiMn 0.6 Fe 0.4 PO4 (LMFP) fills the gaps between NCM811 particles, optimizes the spatial distribution of PVDF binder, constructs a continuous three-dimensional network structure, significantly improves the mechanical strength of the positive electrode sheet, and realizes the active regulation of the needle-puncture internal short circuit mode from the high-risk aluminum current collector-negative active material layer to the safe positive active material layer-negative active material layer.

[0027] 2. This invention enables PVDF to permeate and form an anchoring structure by precisely controlling the porosity (15%~25%) and pore size (5~15µm) of the positive electrode current collector, thereby increasing the interfacial peel strength by more than 30% and giving the current collector controllable fracture characteristics, thus avoiding the overall peeling of the active material layer during needle puncture.

[0028] 3. The present invention coats the diaphragm with an alumina-polyimide composite ceramic coating. The double-sided composite coating takes into account both the thermal stability of the ceramic layer and the fracture toughness of the polyimide layer. The puncture strength is ≥500gf. Only localized and precise damage occurs during needle puncture, which can strictly limit the internal short circuit area. Detailed Implementation

[0029] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0030] In this application, "current collector" refers to a substrate that is conductive in the thickness direction, used to carry the active material layer, and collects and discharges the current generated by the electrodes. It is typically a metal foil or a modified form thereof. Examples include, but are not limited to, aluminum foil, copper foil, surface-roughened or perforated metal foil, and foamed metal current collectors. In this application, the current collector may specifically be a porous aluminum foil with a porosity of 15% to 25%.

[0031] In this application, "porosity" refers to the percentage of pore volume in the current collector or active material layer, used to characterize the material's porosity and liquid permeability. For example, for current collectors, porosity can be achieved through electrochemical etching, laser drilling, or foaming processes; for electrode active material layers, porosity can be controlled by adjusting compaction density and particle size distribution. In this application, the porosity of the porous current collector is controlled at 15%–25%, and the porosity of the composite positive electrode active material layer is controlled at 25%–35%.

[0032] In this application, "positive electrode active material layer" refers to a composite material layer coated or formed on both sides of the positive electrode current collector, composed of electrochemically active materials, conductive agents, and binders, capable of reversibly inserting and de-intercalating lithium ions during charge and discharge. For example, it may include, but is not limited to, coatings composed of layered oxides, olivine-type phosphates, or mixtures thereof. In this application, the positive electrode active material layer is a composite positive electrode active material layer, specifically comprising LiNi... 0.8 Co 0.1 Mn 0.1 O2 (NCM811) and nano-sized lithium manganese iron phosphate (LMFP), with a compaction density of 3.3~3.6 g / cm³. 3 .

[0033] In this application, "negative electrode active material layer" refers to a composite material layer coated or formed on both sides of the negative electrode current collector, consisting of a negative electrode active material capable of reversibly inserting and extracting lithium ions, a conductive agent, and a binder. For example, it may include, but is not limited to, graphite, silicon carbide materials, tin-based materials, lithium titanate, etc. In this application, the negative electrode active material layer specifically includes silicon carbide materials and graphite.

[0034] In this application, "diaphragm" or "separator" refers to a thin film material placed between the positive and negative electrode plates, possessing electronic insulation and ionic conductivity, and capable of preventing short circuits caused by physical contact between the two electrodes. Examples include, but are not limited to: polyolefin microporous membranes (such as polyethylene, polypropylene), nonwoven fabric diaphragms, or their surface-coated modified membranes. In this application, the diaphragm may contain a ceramic-polymer composite coating with a puncture strength of 500 gf or higher.

[0035] In this application, "tab" refers to a metallic conductive component extending from the current collector for conducting internal current to an external circuit, typically a metal sheet or an extension of the current collector's edge. Examples include, but are not limited to, a single tab, multiple tabs, or a full tab structure. In this application, the tab employs a full tab design, meaning that the end face of the current collector in the winding direction serves as the current conduction interface, either entirely or with high coverage.

[0036] In this application, "full tab" structure refers to a battery design in which the end face of the current collector in the winding direction is used as the current conduction interface in a whole or with high coverage, in order to reduce internal resistance and improve current distribution uniformity, rather than using a single or multiple independent tab solder joints. Examples include, but are not limited to: a "tabless" design that is directly welded to the current collector after flattening or cutting the winding end face, or a current collector end face formed by continuous laser cutting of multiple tabs. In this application, the width coverage of the tabs can reach 95% or more.

[0037] In this application, "needle penetration" broadly refers to a test method for assessing the safety of a battery under mechanical abuse, which involves using a conductive object to penetrate the battery casing, causing a direct or indirect short circuit between the internal positive and negative electrodes. For example, this may include, but is not limited to, puncture tests using steel needles, nails, or other sharp objects at different rates and depths. In this application, the test specifically refers to vertically penetrating a φ5mm steel needle at a rate of 5±1mm / s until it completely penetrates the battery under 100% charge.

[0038] In this application, "tab width coverage" generally refers to the ratio of the actual coverage length of the tab along the width direction of the current collector end face to the total width of the current collector end face in a battery with a full tab structure, expressed as a percentage. For example, by flattening or cutting the rolled end face and then directly welding it to the current collector plate, the tab coverage can approach 100%. In this application, the tab width coverage reaches 95% or more.

[0039] In this application, "1C / 600-cycle capacity retention rate" generally refers to the percentage ratio of the battery's discharge capacity after 600 cycles to its initial discharge capacity during a constant current charge-discharge cycle test at room temperature and a 1C rate (i.e., full charge or full discharge completed in 1 hour). This value characterizes the battery's long-term cycle stability. For example, it may include, but is not limited to, values ​​such as 80%, 85%, or 90%. In this application, this capacity retention rate can reach 80% or higher.

[0040] In this application, "electrode expansion rate after 600 cycles" refers to the relative change in thickness of the positive or negative electrode sheet after the same 1C / 600-cycle test as described above. The calculation formula is (average electrode thickness after cycling - average initial electrode thickness) / average initial electrode thickness × 100%. For example, this may include, but is not limited to, the negative electrode being prone to a 10% to 30% thickness increase due to silicon expansion. In this application, the negative electrode expansion rate after 600 cycles can be controlled to be below 15%.

[0041] When lithium-ion batteries are subjected to mechanical abuse such as nail penetration, direct contact can occur between the positive and negative electrodes, resulting in an internal short circuit. This is particularly true for cylindrical batteries employing high-nickel ternary cathode materials (such as LiNi with a high delithiation state). 0.8 Co 0.1 Mn 0.1 In O2 batteries, the dominant internal short-circuit mode is typically the direct contact between the aluminum current collector and the negative electrode active material layer. This short-circuit path has extremely low resistance, generates a large amount of Joule heat in a short time, and triggers a chain of side reactions such as electrolyte decomposition and oxygen release from the positive electrode, leading to rapid thermal runaway of the battery and making it difficult to meet the safety requirements of not catching fire, not exploding, and not emitting smoke.

[0042] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0043] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0045] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.

[0046] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0047] Studies have shown that if the current path of the internal short circuit can be shifted from the low-resistance current collector-negative electrode active material layer interface to a higher-resistance path, the short-circuit current can be limited at the circuit level, suppressing the local temperature rise rate and thus breaking the triggering chain of thermal runaway. Based on this mechanism, the implementation method provided in this specification adopts a multi-dimensional synergistic structural design strategy to actively regulate the internal short circuit-dominant mode to the positive electrode active material layer-negative electrode active material layer mode.

[0048] Based on this, the inventors of this invention achieved it through the following technical solution: A lithium-ion battery includes a housing and an electrode assembly and an electrolyte housed within the housing; The electrode assembly includes a positive electrode plate, a negative electrode plate, a diaphragm, and tabs; The positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector along its thickness direction; the positive active material layer includes a high-nickel ternary material, lithium manganese iron phosphate material, a conductive agent, and a binder; the high-nickel ternary material has the chemical formula LiNi. x Co y Mn z O2, 0.7≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1; the chemical formula of the lithium manganese iron phosphate material is LiMn a Fe b PO4, 0.5≤a≤0.7, 0.3≤b≤0.5, and a+b=1.

[0049] In a preferred embodiment, the high-nickel ternary material has the chemical formula LiNi. 0.8 Co 0.1 Mn 0.1 O2, the chemical formula of lithium manganese iron phosphate material is LiMn 0.6 Fe 0.4 PO4.

[0050] The battery casing can be a hard casing, such as a hard plastic casing, an aluminum casing, a steel casing, etc. Specifically, the casing may include a base plate and a side plate connected to the base plate. The base plate and the side plate enclose a receiving cavity. The casing has an opening communicating with the receiving cavity. A cover plate can be placed on the opening to close the receiving cavity. The electrode assembly is encapsulated in the receiving cavity, and the electrolyte is immersed in the electrode assembly. The present invention does not impose any particular limitation on the shape of the battery, but it is preferably cylindrical.

[0051] In a preferred embodiment, the porosity of the positive electrode current collector is 15% to 25%.

[0052] As an example, the porosity of the positive electrode current collector can be selected as a range of values ​​consisting of 15%, 20%, 25%, or any point values.

[0053] In a preferred embodiment, the peel strength between the positive electrode active material layer and the positive electrode current collector is ≥28 N / m.

[0054] In a preferred embodiment, the compaction density of the positive electrode active material layer is 3.3 g / cm³. 3 ~3.6g / cm 3 The porosity is 25%~35%.

[0055] As an example, the compaction density of the positive electrode active material layer can be specifically chosen to be 3.3 g / cm³. 3 3.5g / cm 3 3.6g / cm 3 Or a range of values ​​composed of any points, preferably 3.5 g / cm³.3 3.6g / cm 3 .

[0056] As an example, the porosity of the positive electrode active material layer can be specifically selected as a range of values ​​consisting of 25%, 30%, 35%, or any point values; preferably 30%.

[0057] In a preferred embodiment, the nanoscale lithium manganese iron phosphate D50 is 200nm~350nm.

[0058] As an example, the nanoscale lithium manganese iron phosphate D50 can be selected as a range of values ​​consisting of 200nm, 250nm, 350nm or any point value.

[0059] In a preferred embodiment, LiNi 0.8 Co 0.1 Mn 0.1 The D50 of O2 is 8µm~12µm.

[0060] In a preferred embodiment, the positive electrode active material layer comprises, by mass percentage, 82% to 88% high-nickel ternary material, 9% to 18% lithium manganese iron phosphate material, 1.2% to 1.8% conductive agent, and 1.2% to 1.8% binder.

[0061] The composite positive electrode active material layer contains at least two types of electrochemically active particles with different lithium intercalation potentials and different electronic conductivities. LiNi is used as an example. 0.8 Co 0.1 Mn 0.1 O2 (NCM811) as the first electrochemically active particle, nano-sized LiMn 0.6 Fe 0.4 Taking PO4 (LMFP) as the second electrochemical active particle as an example, the secondary particles of NCM811 have a D50 of 8µm~12µm, exhibiting low electronic conductivity in the charged state; while the nano-LMFP has a D50 of 200nm~350nm, with a lithium intercalation potential plateau higher than that of graphite anode but lower than that of deeply delithiated NCM811, and relatively low electronic conductivity. When a short circuit is formed by needle penetration, the partial discharge current of the active material layer composed of the two uniformly mixed particles must pass through the electronic and ion conduction network of this composite active material layer. The high resistance in the path limits the amplitude of the short-circuit current, causing the short-circuit heat to be mainly released in the relatively thermally stable positive electrode active material layer region, rather than concentrated at the current collector-anode interface.

[0062] Furthermore, the nano-LMFP particles filling the gaps between micron-sized NCM811 particles in the composite active material layer optimize the spatial distribution of the conductive agent and binder, thereby improving the mechanical strength of the electrode. The compaction density of the positive electrode active material layer can be controlled at 3.3 g / cm³.3 ~3.6g / cm 3 Within this range, the porosity is maintained at 25% to 35%, preserving necessary ion transport channels while taking into account the volumetric energy density.

[0063] The porous current collector possesses penetrating pores with a porosity controlled between 15% and 25%. During the preparation of the positive electrode slurry, the binder can penetrate these pores, forming an anchoring structure after drying and rolling, resulting in a peel strength of over 28 N / m between the composite positive electrode active material layer and the current collector. When a steel needle is inserted, the porous current collector can undergo controlled fracture near the puncture point, preventing the entire active material layer from peeling off from the current collector and thus preventing the formation of a large-area short circuit between the current collector and the negative electrode active material layer.

[0064] In a preferred embodiment, the tab has a width coverage of ≥95%, a rated capacity of 5.0Ah~6.0Ah, a charging cut-off voltage of 4.25V, a discharging cut-off voltage of 2.5V, and an ACR internal resistance of ≤5mΩ.

[0065] It should be understood that the lithium-ion battery in this invention adopts a full-tab winding structure; the tabs here include positive tabs and negative tabs, the positive tab is a metal conductive lead-out terminal extended and cut from the positive current collector; the negative tab is a metal conductive lead-out terminal extended and cut from the negative current collector; the tab width coverage of the positive tab and the negative tab is ≥95% respectively.

[0066] In a preferred embodiment, the thickness of the diaphragm is 6µm to 14µm.

[0067] As an example, the thickness of the diaphragm can be selected as a range of values ​​consisting of 6µm, 8µm, 9µm, 12µm, 14µm, or any point values, preferably 6µm to 9µm.

[0068] In a preferred embodiment, the diaphragm is made of polyethylene.

[0069] In a preferred embodiment, the diaphragm is coated with an alumina-polyimide composite ceramic coating on at least one side along the thickness direction; the thickness of the alumina-polyimide composite ceramic coating is 2µm to 4µm, and the puncture strength is ≥500gf.

[0070] It should be understood that the thickness of the alumina-polyimide composite ceramic coating mentioned here refers to the coating thickness on one side only.

[0071] As an example, the thickness of the alumina-polyimide composite ceramic coating can be selected from a range of values, such as 2µm, 3µm, 4µm, or any combination of points. 2µm is preferred.

[0072] In a preferred embodiment, the negative electrode sheet includes a negative electrode current collector and a layer of negative electrode active material disposed on at least one surface of the negative electrode current collector along the thickness direction.

[0073] In a preferred embodiment, the compaction density of the negative electrode active material layer is 1.5 g / cm³. 3 ~1.7g / cm 3 .

[0074] As an example, the compaction density of the negative electrode active material layer is 1.5 g / cm³. 3 1.6g / cm 3 1.7g / cm 3 Or a range of values ​​composed of any points, preferably 1.6 g / cm³. 3 .

[0075] In a preferred embodiment, the negative electrode active material layer comprises silicon carbon material and graphite; the silicon carbon material accounts for 5% to 25% of the mass of the negative electrode active material layer.

[0076] As an example, the mass percentage of silicon-carbon material in the negative electrode active material layer is 5%, 20%, 25%, or any value within a range, preferably 20%.

[0077] In a preferred embodiment, the electrolyte comprises an electrolyte salt and / or a solvent and / or a film-forming additive; the electrolyte salt comprises lithium hexafluorophosphate; the solvent comprises ethylene carbonate (EC) and / or ethyl methyl carbonate (EMC) and / or dimethyl carbonate (DMC); and the film-forming additive comprises vinylene carbonate and lithium difluorophosphate.

[0078] To further enhance safety, a composite functional diaphragm and a dual-additive electrolyte system were also used. The diaphragm, based on polyethylene, is coated on both sides with an alumina-polyimide composite ceramic coating, exhibiting a puncture strength of no less than 500 gf. This ensures that only localized damage occurs upon needle puncture, strictly limiting the internal short-circuit area. The electrolyte contains vinylene carbonate and lithium difluorophosphate as dual additives, synergistically constructing a composite solid electrolyte interface film at the positive and negative electrode interfaces to suppress continuous exothermic side reactions after needle puncture.

[0079] In a preferred embodiment, the lithium-ion battery is subjected to a φ5mm steel needle puncture test at a rate of 5±1mm / s under 100% SOC fully charged state, and does not catch fire, explode, or emit smoke, with the highest surface temperature of the battery ≤130℃.

[0080] In a preferred embodiment, the lithium-ion battery has a 1C / 600-cycle capacity retention rate of ≥85.0% and an electrode expansion rate of ≤16% after 600 cycles.

[0081] In a preferred embodiment, the lithium-ion battery has a charging cutoff voltage of 4.25V, a discharging cutoff voltage of 2.5V, and a rated capacity of 5.0Ah~6.0Ah; and / or, an ACR internal resistance ≤5mΩ.

[0082] In a second aspect, the present invention provides an electrical device comprising the lithium-ion battery described in any of the preceding claims.

[0083] Based on the aforementioned multi-dimensional synergistic structure, when the battery is subjected to a 5mm diameter steel needle penetration test at a rate of 5±1mm / s under 100% SOC, it can achieve the effects of not catching fire, not exploding, and not emitting smoke, with the highest surface temperature not exceeding 130℃. Simultaneously, the capacity retention rate after 600 cycles at 1C rate is not less than 85.0%, and the electrode expansion rate after 600 cycles does not exceed 16%. The following examples further illustrate the preferred configurations of the positive electrode active material layer composition, the porosity of the porous current collector, the separator coating structure, and the electrolyte additive system, as well as the resulting synergistic effects.

[0084] Example 1 This embodiment provides a high-safety all-tab cylindrical lithium-ion battery, including a housing, an electrode assembly housed within the housing, and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, a separator, and tabs. The positive electrode includes a porous aluminum current collector and a positive electrode active material layer disposed on both sides of the porous aluminum current collector along the thickness direction. The positive electrode active material layer includes LiNi. 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiMn 0.6 Fe 0.4 PO4 (LMFP), in which the conductive agent is superconducting carbon black and carbon nanotubes, and the binder is PVDF.

[0085] The negative electrode includes a copper current collector and negative electrode active material layers disposed on both sides of the copper current collector along the thickness direction; the negative electrode active material layers include silicon carbide material and graphite.

[0086] The diaphragm includes a polyethylene membrane substrate and an alumina-polyimide composite ceramic coating disposed on both sides of the polyethylene membrane substrate.

[0087] The electrolyte comprises an electrolyte salt, a solvent, and a film-forming additive; wherein the electrolyte salt is lithium hexafluorophosphate (LiPF6); the solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC); and the film-forming additive is vinylene carbonate (VC) and lithium difluorophosphate (LiPO2F2).

[0088] The manufacturing process of the aforementioned lithium-ion battery is as follows: Preparation of S1 and nano-LMFP Weigh out LiOH·H2O, MnSO4·H2O, FeSO4·7H2O, and NH4H2PO4 according to stoichiometric ratios, where the Mn:Fe molar ratio is 0.6:0.4 and the Li:(Mn+Fe):P molar ratio is 1:1:1. Add deionized water to prepare a mixed precursor solution with a concentration of 0.5 mol / L. The mixed precursor solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor and kept at 200°C for 12 hours. After natural cooling, it was separated by centrifugation at 8000 rpm for 10 minutes to obtain the olivine-type LMFP precursor. The precursor was mixed and ground with sucrose (sucrose:LMFP mass ratio = 0.1:1), and then calcined at 650℃ for 8h under an argon protective atmosphere with a heating rate of 5℃ / min to obtain carbon-coated nano-LMFP. Carbon-coated nano-LMFP was dispersed in N-methylpyrrolidone (NMP) solvent (solid content 30wt%), and milled in a sand mill at 2000 rpm for 4 h using zirconia ball media to reduce D50 to 250 nm. After filtration, nano-LMFP / NMP dispersion was obtained.

[0089] S2. Preparation of porous aluminum current collectors Take a battery-grade aluminum foil with a thickness of 8µm, ultrasonically clean it in acetone for 10min, then immerse it in a 5% NaOH solution for 30s to remove the surface oxide layer, wash it with water and dry it for later use. A ternary electrolyte system of hydrochloric acid / phosphoric acid / sulfuric acid (volume ratio 5:3:2) was used, with aluminum foil as the anode and graphite plate as the cathode, at a temperature of 25℃ and a current density of 150mA / cm². 2 The aluminum foil was etched for 10 minutes under the specified conditions. After being cleaned in deionized water, it was immersed in a saturated aluminum phosphate solution for passivation for 5 minutes. Then, it was dried in a vacuum oven at 80°C for 2 hours to obtain a porous aluminum current collector with a porosity of 20%.

[0090] S3, Preparation of the positive electrode sheet Based on 100g of dry material, a nano-LMFP / NMP dispersion containing 13g of solid LMFP and 1.5g of PVDF powder were added to a high-speed mixing tank. NMP was added, and the mixture was pre-stirred at 1500rpm for 30min to fully dissolve the PVDF and coat the LMFP particles. Then, 0.75g of superconducting carbon black and 0.75g of carbon nanotubes (CNT, aspect ratio >150) were added, and the mixture was dispersed at 2000rpm for 40min. Finally, 84g of NCM811 (D50=11µm) was added to adjust the solid content to 60wt%, and the mixture was stirred at 3000rpm for 60min. After vacuum degassing, the positive electrode slurry was obtained.

[0091] The positive electrode slurry was coated on both sides of the aforementioned porous aluminum current collector using a slot coating process to form a positive electrode active material layer, with a target double-sided areal density of 35.0 mg / cm³. 2 After drying in four drying tunnels (100 / 110 / 120 / 130℃, each section for approximately 80 seconds), it is rolled to a compacted density of approximately 3.50 g / cm³. 3 After cutting, a positive electrode sheet is obtained; the porosity of the positive electrode active material layer is 30%, the D50 of the LMFP is 250nm, and the peel strength between the positive electrode active material layer and the porous aluminum current collector is 32N / m.

[0092] S4, Preparation of the negative electrode sheet Weigh out 20.0% deposited silicon carbide, 76.0% graphite, 0.5% single-walled carbon nanotubes, 0.9% conductive carbon black, 1.0% sodium carboxymethyl cellulose, 0.8% polyacrylic acid and 0.8% styrene-butadiene rubber by weight percentage; The above substances were added to deionized water and stirred to form a negative electrode slurry (solid content 50%), which was then coated on both sides of an 8µm thick copper current collector. After drying at 100℃ for 20 min and cold pressing at 8MPa, a negative electrode sheet was obtained with a compaction density of 1.6 g / cm³. 3 .

[0093] S5. Preparation of the diaphragm α-Al2O3 powder with D50=400nm was mixed with polyimide precursor (polyamic acid, PAA, dissolved in NMP) at a mass ratio of 7:3, the solid content was adjusted to 20wt%, 0.5wt% polyvinylpyrrolidone was added as a dispersant, and after high-speed dispersion, it was ground until the slurry particle size D90<1µm to obtain Al2O3-PAA composite coating slurry; Using an 8µm thick polyethylene film as the substrate, Al2O3-PAA composite slurry was coated on both sides by a micro-gravure roller coating method. After pre-drying at 120℃ for 1 min, it was subjected to thermal imidization at 200℃ for 5 min to completely convert PAA into PI. The single-sided coating shrank to 2µm to obtain a composite functional diaphragm with a total thickness of 12µm and a puncture strength of 530gf.

[0094] S6. Preparation of electrolyte In a dry room with a dew point ≤ -40℃, LiPF6 was dissolved in a mixed organic solvent of EC / EMC / DMC with a volume ratio of 1:1.2:0.8 to prepare a basic electrolyte with a concentration of 1.2 mol / L. Then, 1.5 wt% vinylene carbonate (VC) and 0.8 wt% lithium difluorophosphate (LiPO2F2) were added sequentially and stirred until completely dissolved. The electrolyte was allowed to stand at 25℃ for 12 h to mature. After the moisture content was ≤20 ppm, the electrolyte was sealed for later use.

[0095] S7, Battery Assembly After the positive and negative electrode sheets are rolled and slit, they are wound together with the separator according to the set process to form a 21700 cylindrical battery core with a tab width coverage of 97%. The battery core is fixed to the connecting piece by welding and installed in a metal battery casing. Electrolyte is injected, and after sealing and formation, the lithium-ion battery of Example 1 is obtained (rated capacity 5.2Ah, ACR internal resistance 4.3mΩ, charging cut-off voltage 4.25V, discharging cut-off voltage 2.5V).

[0096] Comparative Example 1 Compared with Example 1, Comparative Example 1 differs in that the dry composition of the positive electrode slurry is: 97g NCM811, 0.75g superconducting carbon black SP, 0.75g carbon nanotubes (CNTs), and 1.5g PVDF, with a solid content of 60wt%. The slurry preparation process is as follows: PVDF powder is dissolved in NMP, SP and CNTs are added and dispersed evenly, and finally NCM811 is added and stirred at 3000rpm for 60min. After vacuum degassing, the mixture is coated onto a 20% porosity porous aluminum current collector (double-sided), with a target double-sided surface density of 35.0mg / cm³. 2 Rolled to a compaction density of 3.50 g / cm³ 3 The remaining procedures are the same as in Example 1.

[0097] Example 2 The only difference between Example 2 and Example 1 is that the amount of solid LMFP (i.e. the amount of solid in the LMFP / NMP dispersion) is 12g, and the amount of NCM811 is adjusted to 85g accordingly.

[0098] Example 3 The only difference between Example 3 and Example 1 is that the amount of solid LMFP (i.e. the amount of solid in the LMFP / NMP dispersion) is 11g, and the amount of NCM811 is adjusted to 86g accordingly.

[0099] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the amount of solid LMFP (i.e., the amount of solid in the LMFP / NMP dispersion) is 20g, and the amount of NCM811 is adjusted to 77g accordingly.

[0100] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that ordinary 8µm battery-grade aluminum foil is used. It is not subjected to electrochemical etching to create holes, but is directly used for positive electrode coating after only ultrasonic cleaning with acetone and degreasing with NaOH. The remaining processes are the same as in Example 1.

[0101] Example 4 The only difference between Example 4 and Example 1 is that the electrochemical corrosion uses a ternary electrolyte of hydrochloric acid / phosphoric acid / sulfuric acid (volume ratio 5:3:2) and a current density of 150 mA / cm². 2At a temperature of 25℃ and a corrosion time of 6 minutes, a porous aluminum current collector with a porosity of 15% was obtained.

[0102] Example 5 The only difference between Example 5 and Example 1 is that the electrochemical corrosion uses a ternary electrolyte of hydrochloric acid / phosphoric acid / sulfuric acid (volume ratio 5:3:2) and a current density of 150 mA / cm². 2 At a temperature of 25℃ and a corrosion time of 10 minutes, a porous aluminum current collector with a porosity of 20% was obtained. The water washing, passivation, drying and inspection processes were the same, as were the positive electrode coating, rolling and assembly processes.

[0103] Example 6 The only difference between Example 6 and Example 1 is that the electrochemical corrosion uses a ternary electrolyte of hydrochloric acid / phosphoric acid / sulfuric acid (volume ratio 5:3:2) and a current density of 150 mA / cm². 2 At a temperature of 25℃ and a corrosion time of 12 minutes, a porous aluminum current collector with a porosity of 25% was obtained. The water washing, passivation, drying, and inspection processes were the same, as were the positive electrode coating, rolling, and assembly processes. Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the electrochemical corrosion used a ternary electrolyte of hydrochloric acid / phosphoric acid / sulfuric acid (volume ratio 5:3:2) and a current density of 150 mA / cm². 2 At a temperature of 25℃ and a corrosion time of 15 minutes, a porous aluminum current collector with a porosity of 30% was obtained. The water washing, passivation, drying and inspection processes were the same, as were the positive electrode coating, rolling and assembly processes.

[0104] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that a 9µm PE base film was used directly without any coating, while the rest of the procedures were the same as in Example 1.

[0105] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is that a 9µm PE film was used as the substrate, and an Al2O3 coating (without PI precursor) was applied to only one side using a micro-gravure roller coating method. The coating thickness was 3µm, and the film was dried at 120°C for 2 minutes without thermal imidization treatment.

[0106] Example 7 The only difference between Example 7 and Example 1 is that 9µm PE film is used as the substrate, and double-sided coating is performed using microgravure roller coating method, with a single-sided coating thickness of 2µm. The thermal imidization conditions are the same as in Example 1.

[0107] Example 8 The only difference between Example 8 and Example 1 is that the PE substrate thickness is 6µm, the single-sided coating is 3µm, the double-sided coating is done by micro-gravure roller coating, and the thermal imidization conditions are the same as in Example 1.

[0108] Example 9 The only difference between Example 9 and Example 1 is that the PE substrate thickness is 6µm, the single-sided coating is 4µm, the double-sided coating is done by micro-gravure roller coating, and the thermal imidization conditions are the same as in Example 1.

[0109] Comparative Example 7 The only difference between Comparative Example 7 and Example 1 is that a 12µm PE film is used as the substrate, and pure Al2O3 slurry (without PI precursor) is coated on both sides, with a single-sided thickness of 2µm, and dried at 120°C for 2 min.

[0110] Example 10 The only difference between Example 10 and Example 1 is that the concentration of LiPF6 is 1.1 mol / L, the content of VC is 1 wt%, the content of LiPO2F2 is 0.5 wt%, and the volume ratio of EC:EMC:DMC is 1:1.2:0.8.

[0111] Example 11 The only difference between Example 11 and Example 1 is that the concentration of LiPF6 is 1.2 mol / L, the content of VC is 2 wt%, the content of LiPO2F2 is 1 wt%, and the volume ratio of EC:EMC:DMC is 1:1.2:0.8.

[0112] Example 12 The only difference between Example 12 and Example 1 is that the concentration of LiPF6 is 1.3 mol / L, the content of VC is 1.5 wt%, the content of LiPO2F2 is 0.8 wt%, and the volume ratio of EC:EMC:DMC is 1:1:1.

[0113] Comparative Example 8 The only difference between Comparative Example 8 and Example 1 is that the concentration of LiPF6 in the electrolyte is 1.2 mol / L, the content of VC is 0 wt%, the content of LiPO2F2 is 0 wt%, the volume ratio of EC:EMC:DMC is 1:1.2:0.8, and there are no film-forming additives.

[0114] Comparative Example 9 The only difference between Comparative Example 9 and Example 1 is that the concentration of LiPF6 in the electrolyte is 1.2 mol / L, the content of VC is 1.5 wt%, the content of LiPO2F2 is 0 wt%, and the volume ratio of EC:EMC:DMC is 1:1.2:0.8.

[0115] Comparative Example 10 The only difference between Comparative Example 10 and Example 1 is that the concentration of LiPF6 in the electrolyte is 1.2 mol / L, the content of VC is 0 wt%, the content of LiPO2F2 is 0.8 wt%, and the volume ratio of EC:EMC:DMC is 1:1.2:0.8.

[0116] Tests conducted by relevant testing parties: First, the lithium-ion battery was constant-current discharged to 2.5V to ensure it was in a safe state, reducing the risk of short circuits or thermal runaway during disassembly. Inside a glove box (protected by argon or other inert atmosphere), the battery was carefully disassembled, and the positive electrode of the cylindrical cell was removed. The electrode was peeled off using tweezers or a suitable tool. Next, the removed positive electrode was cut to an appropriate size and immersed in anhydrous dimethyl carbonate (DMC) solution for 30 minutes to dissolve and remove residual electrolyte and possible byproducts. After removing the electrode, the surface active material was wiped off with lint-free paper, and then the immersion-wiping process was repeated three times with fresh DMC solution to ensure no residual active layer remained on the electrode surface. Subsequently, the electrode was rinsed with anhydrous ethanol and wiped again to further remove solvent and impurities. After cleaning, the electrode was placed in the glove box and left to stand for 48 hours to ensure the primer current collector was completely dry, preventing interference from solvent residue in subsequent tests. The dried primer current collector was then used for subsequent testing.

[0117] Cylindrical cell specification and dimension measurement: Using vernier calipers with an accuracy of at least 0.02 mm, physical measurements were performed on the finished cylindrical batteries at room temperature (25°C). The diameter was measured along the uniform cylindrical section of the battery casing; the overall height was measured from the bottom of the battery casing to the highest point of the top cover, as follows: Determination of porosity of aluminum current collector: The mercury intrusion porosimetry method was used. The positive electrode sheet was cut to an appropriate area and immersed in anhydrous dimethyl carbonate for washing three times to remove residual electrolyte and active material. After drying in a vacuum oven at 80℃ for 12 hours, multiple samples were stacked in the dilatometer of the mercury intrusion porosimeter. Mercury intrusion tests were performed sequentially in the low-pressure section (0.003~0.2MPa) and the high-pressure section (0.2~414MPa). The contact angle of mercury was set to 140° and the surface tension to 480mN / m. The pore size distribution and cumulative pore volume were calculated according to the Washburn equation. The porosity of the current collector was the percentage obtained by dividing the cumulative pore volume within the pore size range of 1~50µm by the geometric volume of the sample.

[0118] Determination of the peel strength between the positive electrode active material layer and the current collector: A long strip sample was fixed to a flat thin steel plate with double-sided tape. The protective layer of the double-sided tape was removed, and the exposed aluminum current collector side of the positive electrode sheet to be tested was adhered to the double-sided tape. A pressure roller was used to evenly press the sample to ensure adhesion. The unattached end was peeled off, and the peeled electrode sheet was bent upwards and clamped in the upper fixture of a tensile testing machine for a 180° peel test. The tensile force curve was recorded. A stable peel segment was selected where the tensile force change did not exceed 10%. The average tensile force of this segment was divided by the electrode sheet width to obtain the peel strength. Tests were performed on the front, middle, and rear segments of the electrode sheet, and the arithmetic mean was taken.

[0119] Diaphragm puncture strength: Fix the diaphragm to the test fixture, puncture vertically with a 1mm diameter ball needle at a rate of 50mm / min, and record the maximum puncture force, referring to GB / T 36363.

[0120] Determination of compaction density: The electrode sheets, after being washed with dimethyl carbonate and vacuum dried, were cut into nine standard-sized square samples (2.0cm × 2.0cm). Three of these samples were used to remove the active material from both sides, rinsed with NMP, dried, weighed, and the average mass M1 was calculated. The average thickness L1 was also measured. The remaining three samples were weighed to obtain the average mass M2, and the average thickness L2 was measured. The compaction density was calculated using the following formula: P = (M2 - M1) / (2 × 2 × (L2 - L1)).

[0121] Method for determining the rated capacity of cylindrical batteries: The rated capacity of cylindrical batteries is usually determined under standard room temperature conditions (e.g., 25±2℃). The specific steps are as follows: First, the formed battery is charged to standard current at a set standard current (usually 0.2C) to the rated upper limit voltage (e.g., 4.25V). Then, it is switched to constant voltage charging until the current drops to the specified cutoff value (e.g., 0.05C) and left to stand for 30 minutes to achieve internal electrochemical equilibrium. Next, the fully charged battery is continuously discharged at a standard discharge current (usually 0.2C constant current) until the voltage drops to the discharge cutoff voltage specified in the product specification (e.g., 2.5V). During this discharge stage, the total amount of electricity released (i.e., ampere-hour integral) is recorded and calculated using a high-precision battery test cabinet.

[0122] Method for determining ACR internal resistance: Place the battery under test in a constant temperature environment of 25±2°C for more than 2 hours to ensure that the battery reaches thermal equilibrium and the open circuit voltage is stable; use an AC internal resistance tester to apply an AC constant current signal with a frequency of 1kHz and an effective value of 0.1C~0.2C, and measure the AC impedance amplitude of the battery, which is the ACR internal resistance, in mΩ.

[0123] Cyclic performance test: After placing the battery in a 25℃ constant temperature chamber for 6 hours, the following steps were performed: For the first cycle, charge at a constant current of 1C to 4.25V, then switch to constant voltage charging until the current drops to 0.1C, let stand for 30 minutes, and then discharge at 1C to 2.5V; subsequently, charge at a constant current of 1C to 4.25V, let stand for 30 minutes, and then discharge at 1C to 2.5V, repeating this charge-discharge cycle for a total of 600 cycles. Record the discharge capacities Q1 and Q600 for the 1st and 600th cycles. Capacity retention rate = (Q600 / Q1) × 100%.

[0124] Determination of electrode expansion rate after 600 cycles: After 600 cycles, the battery was disassembled under an inert atmosphere. The electrodes were removed, cleaned by soaking in dimethyl carbonate, and dried. The thickness of the electrodes at nine points was measured using a micrometer, and the average value T600 was taken. Electrode expansion rate = ((T600-T0) / T0) × 100%, where T0 is the initial thickness of the dried electrodes before cycling.

[0125] Needle penetration test: Fully charge the battery to be tested to 100% SOC and let it stand in a 25℃ environment for 2 hours. Fix the battery on an insulating clamp and use a 5mm diameter stainless steel needle, perpendicular to the battery surface, to penetrate the battery at a constant speed of 5±1mm / s until it is completely penetrated. Keep the needle still and observe for 5 minutes, recording whether fire, explosion, smoke, and the highest surface temperature monitored by the thermocouple attached to the battery surface occur.

[0126] The test results are shown in Tables 1 to 4.

[0127] Table 1. Single-factor validation of the proportion of nano-LMFP addition. As shown in Table 1, in the single-factor experiment where all other preparation conditions remained unchanged and only the amount of nano-LMFP added was varied, Comparative Example 1 without LMFP caught fire / exploded during the 100% SOC needle penetration test, with the highest surface temperature exceeding 300°C, a capacity retention rate of only 82.3% after 600 cycles, and an electrode expansion rate as high as 19.2%, indicating that the pure NCM811 cathode system has serious safety hazards under abusive needle penetration conditions. With the introduction of LMFP (Examples 2 and 3), the needle penetration safety was significantly improved, and the batteries did not catch fire, explode, or emit smoke. The highest surface temperature dropped to 116~122°C, the cycle retention rate increased to over 86%, and the electrode expansion rate dropped to 15%~16%. This indicates that nano-LMFP effectively controlled the internal short-circuit mode and suppressed thermal runaway by filling the gaps between NCM811 particles and constructing a continuous three-dimensional network structure. Taking Example 1 (LMFP) as an example, The optimal ratio, represented by 13 parts, achieved the best performance in three indicators: needle penetration safety (maximum temperature 112℃), cycle retention rate (87.5%), and electrode expansion rate (14.8%). In contrast, the comparative example 2, which had excessive LMFP, had acceptable needle penetration safety, but its rated capacity decreased to 4.6Ah, its ACR internal resistance increased to 5.8mΩ, and its cycle retention rate deteriorated to 79.8%. This indicates that excessive LMFP dilutes the positive electrode active material, increases electrode resistance, and causes a significant decline in electrochemical performance. Therefore, there is an optimal range for the amount of LMFP added; too little is insufficient to ensure safety, while too much sacrifices electrochemical performance.

[0128] Table 2. Single-factor verification of porosity in porous aluminum current collectors. As shown in Table 2, in the single-factor experiment where the positive electrode formulation, separator, and electrolyte conditions remained unchanged, but only the porosity of the aluminum current collector was changed, Comparative Example 3, using a smooth aluminum current collector, ignited during the 100% SOC needle penetration test, with the highest surface temperature exceeding 250°C. After 600 cycles, the capacity retention rate was only 83.5%, and the electrode expansion rate was as high as 18.8%. This was due to insufficient interfacial peel strength between the smooth aluminum and the active material layer, leading to the overall peeling of the active layer and expansion of the internal short-circuit area during needle penetration, making thermal runaway difficult to suppress. With the introduction and improvement of the current collector porosity (Examples 4, 5, and 6), the PVDF binder penetrated into the pores to form an anchoring structure, significantly enhancing the interfacial peel strength and greatly improving needle penetration safety. All three examples achieved no fire, no explosion, and no smoke, with the highest surface temperature reduced to 113-119°C, the cycle retention rate increased to over 86%, and the electrode expansion rate decreased to around 15%. Among them, Example 1 (with a high porosity) showed the best performance. The optimal solution, represented by a porosity of 20%, showed the best overall performance in five indicators: safety (maximum temperature 112℃), capacity (5.2Ah), internal resistance (4.3mΩ), cycle retention (87.5%), and electrode expansion rate (14.8%). In contrast, although the comparative example 4, with excessive porosity, did not catch fire during needle penetration, the mechanical strength of the current collector itself decreased due to excessive pore formation, resulting in a drop in rated capacity to 4.8Ah, an increase in ACR internal resistance to 5.5mΩ, and a deterioration in cycle retention to 80.1%. This indicates that there is a reasonable upper limit to porosity. Excessive porosity sacrifices the structural integrity of the current collector and also impairs electrochemical performance. Therefore, controlling the porosity of porous aluminum current collectors within the range of 15% to 25% is the optimal choice that balances needle penetration safety and overall battery performance.

[0129] Table 3 Single-factor validation of composite functional membrane coating structure As shown in Table 3, in the single-factor experiment where the positive electrode formulation, porous aluminum current collector, and electrolyte conditions remained unchanged, but only the membrane coating structure was altered, Comparative Example 5, with an uncoated membrane, ignited and emitted smoke during the 100% SOC needle penetration test, with the highest surface temperature exceeding 280°C and an electrode expansion rate as high as 20.1%. This indicates that the thermal stability and puncture strength of the ordinary PE membrane are insufficient, and the large-area damage to the membrane during needle penetration led to the uncontrolled internal short circuit. Comparative Example 6, with a single-sided Al2O3 coating, improved the thermal stability of the membrane to some extent, but still emitted smoke during needle penetration, with the highest temperature reaching 175°C. This is because the single alumina coating has limited fracture toughness and is prone to brittle fracture during needle penetration. Furthermore, the single-sided coating caused the membrane to warp due to heat, making it difficult to effectively limit the internal short circuit. Examples 7, 8, and 9, which used a double-sided Al2O3-PI composite coating, all achieved no fire, explosion, or smoke, and the highest surface temperature was reduced to 115~121°C. The cycle retention rate reached over 86%, and the electrode expansion rate decreased to around 15%, indicating that the dual synergistic mechanism of the alumina layer providing thermal stability and the polyimide layer providing fracture toughness can achieve precise local damage and strictly limit the internal short-circuit area during needle penetration. Among them, Example 1 (8µm substrate + 2µm single-sided coating) has the best overall performance. Although the needle penetration safety of Comparative Example 7, which has an excessively thick separator, is still acceptable, the rated capacity drops to 4.5Ah, the ACR internal resistance rises to 5.6mΩ, and the cycle retention rate deteriorates to 81.3%. This shows that the excessively thick separator significantly occupies the internal space of the battery, increases the ion transport resistance, and causes a significant loss in energy density and power performance. Therefore, the substrate thickness and coating thickness of the composite functional separator need to achieve a reasonable balance between safety protection and electrochemical performance.

[0130] Table 4 Single-factor validation of electrolyte dual additives Table 4 shows that in the single-factor experiment where the positive electrode formulation, porous aluminum current collector, and composite functional separator conditions remained unchanged, but only the type and amount of electrolyte additives were varied, Comparative Example 8 without additives ignited during the 100% SOC needle penetration test, with the highest surface temperature exceeding 260℃. After 600 cycles, the capacity retention rate was only 80.5%, and the electrode expansion rate was as high as 20.5%. This indicates that the basic electrolyte could not effectively suppress the exothermic side reaction at the interface after the needle penetration triggered an internal short circuit, and the thermal runaway chain reaction spread rapidly. Comparative Example 9 with added VC and Comparative Example 10 with added LiPO2F2 alone reduced the highest needle penetration temperature to 165℃ and 158℃ respectively, but both showed smoke, and the cycle retention rate only increased to about 83%. This indicates that the SEI film constructed with a single additive has significant deficiencies in quality and stability, and can only partially suppress the exothermic side reaction, failing to fundamentally address the problem. The upper part blocks thermal runaway; while the VC and LiPO2F2 dual additive synergistic scheme in Examples 10, 11 and 12 all achieve no fire, no explosion and no smoke, the highest surface temperature is reduced to 113~120℃, the cycle retention rate is increased to more than 86%, and the electrode expansion rate is reduced to about 15%. This is because VC preferentially reduces to form a dense organic SEI framework on the negative electrode surface, while LiPO2F2 provides inorganic lithium fluoride components to enhance the ionic conductivity and thermal stability of the SEI film. The high-quality composite SEI film constructed by the two can effectively suppress the continuous exothermic side reaction of the electrolyte and electrode materials after the needle penetration internal short circuit occurs. Among them, Example 1 (VC 1.5wt% + LiPO2F2 0.8wt%) has the best comprehensive performance in terms of safety and electrochemical performance, which further confirms that the synergistic effect of the dual additive system is the key electrolyte design strategy to achieve the synergistic improvement of needle penetration safety and long cycle stability.

[0131] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0132] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0133] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion battery, characterized in that, The lithium-ion battery includes a housing and an electrode assembly and an electrolyte housed within the housing; The electrode assembly includes a positive electrode plate, a negative electrode plate, a diaphragm, and tabs; The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector along its thickness direction; the positive active material layer includes a high-nickel ternary material, lithium manganese iron phosphate material, a conductive agent, and a binder; the high-nickel ternary material has the chemical formula LiNi. x Co y Mn z O2, 0.7≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, and x+y+z=1; the chemical formula of the lithium manganese iron phosphate material is LiMn a Fe b PO4, 0.5≤a≤0.7, 0.3≤b≤0.5, and a+b=1.

2. The lithium-ion battery according to claim 1, characterized in that, The chemical formula of the high-nickel ternary material is LiNi. 0.8 Co 0.1 Mn 0.1 O2, the chemical formula of the lithium manganese iron phosphate material is LiMn 0.6 Fe 0.4 PO4.

3. The lithium-ion battery according to claim 1, characterized in that, The porosity of the positive electrode current collector is 15%~25%; and / or, The peel strength between the positive electrode active material layer and the positive electrode current collector is ≥28 N / m.

4. The lithium-ion battery according to claim 2, characterized in that, The compaction density of the positive electrode active material layer is 3.3 g / cm³. 3 ~3.6g / cm 3 Porosity is 25%~35%; and / or, The LiMn 0.6 Fe 0.4 The D50 of PO4 is 200nm~350nm; the LiNi 0.8 Co 0.1 Mn 0.1 The D50 of O2 is 8µm~12µm.

5. The lithium-ion battery according to claim 1, characterized in that, The positive electrode active material layer comprises, by mass percentage, 82%-88% high-nickel ternary material, 9%-18% lithium manganese iron phosphate material, 1.2%-1.8% conductive agent, and 1.2%-1.8% binder.

6. The lithium-ion battery according to claim 1, characterized in that, The thickness of the diaphragm is 6µm to 14µm; and / or, The diaphragm is made of polyethylene; and / or, The diaphragm is coated with an alumina-polyimide composite ceramic coating on at least one side along its thickness direction; the thickness of the alumina-polyimide composite ceramic coating is 2µm~4µm, and the puncture strength is ≥500gf.

7. The lithium-ion battery according to claim 1, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector along the thickness direction; The compaction density of the negative electrode active material layer is 1.5 g / cm³. 3 ~1.7g / cm 3 ; and / or, The negative electrode active material layer comprises silicon carbon material and graphite; the silicon carbon material accounts for 5%-25% of the mass of the negative electrode active material layer.

8. The lithium-ion battery according to claim 1, characterized in that, The electrolyte comprises an electrolyte salt and / or a solvent and / or a film-forming additive; the electrolyte salt comprises lithium hexafluorophosphate; the solvent comprises ethylene carbonate and / or ethyl methyl carbonate and / or dimethyl carbonate; and the film-forming additive comprises vinylene carbonate and lithium difluorophosphate.

9. The lithium-ion battery according to any one of claims 1 to 8, characterized in that, The lithium-ion battery was subjected to a φ5mm steel needle puncture test at a rate of 5±1mm / s under 100% SOC fully charged state. It did not catch fire, explode, or emit smoke, and the highest surface temperature of the battery was ≤130℃.

10. The lithium-ion battery according to any one of claims 1 to 8, characterized in that, The lithium-ion battery has a 1C / 600-cycle capacity retention rate of ≥85.0%; and / or, After 600 cycles, the electrode expansion rate is ≤16%; and / or, The charging cut-off voltage is 4.25V, the discharging cut-off voltage is 2.5V, and the rated capacity is 5.0Ah~6.0Ah; and / or, the ACR internal resistance is ≤5mΩ.

11. An electrical appliance, characterized in that, The electrical equipment includes the lithium-ion battery as described in any one of claims 1 to 10.